Design Greatest Hits: Design's best-selling hits - García Garrido, Sebastián (I+Diseño. Revista Científica de Investigación y Desarrollo en Diseño, 2011)
Design Greatest Hits closes the third cycle of exhibitions on design and innovation, which has been developed since 2007 by the Sociedad Estatal ddi, and the Círculo de Bellas Artes de Madrid. The organisation is owned by ENISA, since it comprises the aforementioned entity, whose exhibition will be open to the public until the end of January.